Parent Income-Based Gaps in Schooling - Kathleen M. Ziol-Guest; Kenneth T. H. Lee (SAGE Publishing, 2016)
Both income inequality and the achievement test score gap between high- and low-income children increased dramatically in the United States beginning in the 1970s. Recent work by Chetty, Hendren, Kline, Saez, and Turner (2014) suggests that, unlike the test score gap, the gap in college enrollment is essentially constant. This article takes a longer historical view and investigates trends in income-based gaps in a number of schooling attainment measures using data from two cohorts of the National Longitudinal Survey of Youth (NLSY79 and NLSY97) as well as 31 birth cohorts from the Panel Study of Income Dynamics (PSID). Findings support Chetty and colleagues' conclusion of little change in college enrollment for their cohorts but show significant increases in college enrollment gaps between Chetty and colleagues' and prior cohorts in both the PSID and the NLSY. We further find strong evidence of growing gaps in college completion. In contrast, gaps in high school graduation have fallen, which provide at least one optimistic sign of catching up among low-income individuals. The net result of these trends is to produce a modestly increasing gap in completed schooling between children growing up in low- and high-income families.